Efektivitas Kepatuhan Wajib Pajak, Pemeriksaan Pajak dan Penagihan Pajak terhadap Penerimaan Pajak - Andini Pratiwi; Adinda Aghnia Khairunnisa; Agiel Delvinza Ramadhandy; Aisyah Eka Savitri (Penerbit Goodwood, 2024)
Purpose: This study analyzes the effectiveness of taxpayer compliance, tax audits, and tax collection on tax revenue. Research methodology: This study analyzes data from the period of 2021-2023, which covers financial revenues from various sources. Results: The research findings indicate the significant role of taxpayer compliance, tax audits, and tax collection in enhancing tax revenue. Limitations: The limitations of this research are as follows: (1) the variables used are limited to three, namely taxpayer compliance, tax inspection, and tax collection; (2) this study is still in the form of a narrative; and (3) this research only utilizes a literature review as the method. Contribution: This study is expected to provide readers with knowledge regarding the effectiveness of taxpayer compliance, tax audits, and tax collection on tax revenue.